ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTELLECTUAL CAPITAL DISCLOSURE(ICD) - Stephani, Thresya; Yuyetta, Etna Nur Afri (JURNAL AKUNTANSI DAN AUDITING, 2011)
Increased attention regarding intellectual capital as a dominant factor in the growingcompetitiveness and strength of a firm has encouraged the organizations to disclose theirintellectual capital. This study aims to analyze the factors that affect the disclosure of intellectualcapital, namely firm size, firm age, leverage, profitability, and type of auditor in a firm. Thesamples used were secondary data from the Indonesia Stock Exchange (IDX) Annual Report ofmanufacturing companies listed on the Stock Exchange in 2008-2010. Samples were taken witha purposive sampling method, and who meet the criteria for sample selection. This study usesMultiple Linear Regression Analysis, with t statistics test the hypothesis testing and statistical testF. The results showed that firm size, leverage, and type of auditor affect the intellectual capitaldisclosure(ICD). However, firm age and profitability has no effect on ICD